Analysis of pCl107 a large plasmid carried by an ST25 Acinetobacter baumannii strain reveals a complex evolutionary history and links to multiple antibiotic resistance and metabolic pathways. (18th November 2022) - Rafei, Rayane; Koong, Jonathan; Osman, Marwan; Al Atrouni, Ahmad; Hamze, Monzer; Hamidian, Mehrad
Abstract: Acinetobacter baumannii has successfully spread during the last decades as one of the main critically important pathogens. However, many aspects including plasmids, are still under-investigated. Here, we report the complete sequence of an Acinetobacter baumannii strain, belonging to the ST25 IP (Institut Pasteur) sequence type recovered in 2012 in Lebanon, using a combination of Illumina MiSeq and Oxford Nanopore sequencing and a hybrid assembly approach. This strain (Cl107) carries a 198 kb plasmid called pCl107 that encodes the MPFI conjugative transfer system. The plasmid carries the aacA1, aacC2, sul2, strAB, and tetA (B) antibiotic resistance genes. pCl107 region encompassing the sul2, strAB, tetA (B) is closely related to AbGRI1 chromosomal resistance islands, which are widespread in A. baumannii strains belonging to Global Clone 2. The resistance region found in pCl107 is one of the missing links in the evolutionary history of the AbGRI1 islands. pCl107 also contains a BREX Type 1 region and represents one of the two main evolution patterns observed in BREX clusters found in plasmids related to pCl107. pCl107 also harbours a ptx phosphonate metabolism module, which plays an ancestral structure compared to other large plasmids in ST25 strains. While the uric acid metabolic module found in pCl107 is incomplete, we identified possible ancestors from plasmids and chromosomes of Acinetobacter spp. Our analyses indicate a complex evolutionary history of plasmids related to pCl107 with many links to multiple antibiotic resistance and metabolic pathways.